The Position of E-Commerce that Causes Default in the Perspective of Fiqh Muamalah - Sari, Muspita; Hidayat, LD Dian; Jasmin, Suriah Pebriyani (Al-'Adl, 2024)
With the ease of accessing the internet and the advancement of technology, the system of buying and selling has become easily accessible anytime and anywhere. The objective of this study is to uncover the e-commerce system in online buying and selling conducted by students of IAIN Bone, the emergence of various online shopping sites such as Lazada, Shopee, Tiktok Shop, Tokopedia, Bukalapak, and various other online shopping sites, resulting in violations known as breach of contract. Using empirical research and data collection based on survey results to students who use online shopping site applications during the year 2023. The results show that students who generally use online shopping sites through the e-commerce system experience breach of contract where the goods received do not match what was promised. The percentages are as follows: 36% on Shopee, 29% on Tiktok Shop, 21% on Lazada, 9% on Bukalapak, and 5% on Tokopedia.